Design and Development of Composite Propellant Using CuFe2O4 Spinel Decorated Graphene Oxide Nanocomposite as Novel Burn Rate Modifier. Issue 11 (26th October 2022) - Ar, Guruvayurappan; Dhas, Akash M.; Pawar, R. B.; Banerjee, Shaibal
Abstract: The burning rate of composite rocket propellant is a principal ballistic property that is considered while designing the rocket motor. Carbon bonded materials such as CNT(carbon nanotubes), fullerene, graphene, etc. due to their high surface area have exhibited promising results as burn rate modifiers in a propellant. Apart from enhancing the burn rate, unlike their inorganic counterparts, they are combustible and contribute towards energy output. Herein, we report a spinel structure CuFe2 O4 decorated Graphene Oxide nanocomposite as novel burn rate modifier (BRM) in propellant composition. By incorporating 0.6 % of this burn rate modifier to the propellant remarkable improvement in burn rate by 61 % was observed. Abstract :